THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY AND CAPITAL INTENSITY TO AGGRESSIVENESS A TAX ON MINING COMPANIES THAT: REGISTERED AT THE INDONESIAN STOCK EXCHANGE A PERIOD OF THE YEAR 2011 â€“ 2015 - Ambarita, Sulastri; Pakpahan, Johnson; Sidharta, Juaniva (Universitas Kristen Indonesia, 2017)
The purpose of this research to know whether there were influence corporate social responsibility (CSR) and capital intensity of tax aggressiveness company. Independent variable used in research is disclosure of corporate social responsibility and capital intensity, while dependent variable the research is aggressiveness tax. The data used funded by primary data company to a period of five years from 2011 up to 2015. The methodology used writer is the kind of research causal, to know relations independent variable and dependent variable. The hypothesis used is H0 :Î²i = 0 (no influence between CSR and capital intensity to aggressiveness taxes). HA : Î²i â‰ 0 (Is influence between CSR and capital intensity to aggressiveness taxes). Significant level of used 0.05 if the value of the significance of smaller than 5 percent free Independent variable significant on dependent variables. This research result indicates that CSR and capital intensity simultaneously not affect significantly to aggressiveness tax .Keywords: CSR, capital intensity, aggressiveness tax.